2019
DOI: 10.3389/fpls.2018.01940
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Naphthazarin on the Growth, Electrogenicity, Oxidative Stress, and Microtubule Array in Z. mays Coleoptile Cells Treated With IAA

Abstract: Naphthazarin (5,8-dihydroxy-1,4-naphthoquinone, DHNQ) is a naturally occurring 1,4-naphthoquinone derivative. In this study, we focused on elucidating the toxic effect of this secondary metabolite on the growth of plant cells. The dose–response curves that were obtained for the effects of DHNQ on endogenous and IAA-induced growth in maize coleoptile segments differ in shape; in the first case, it is linear, while in the presence of auxin it is bell-shaped with the maximum at 1 μM. It was found that DHNQ at alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 91 publications
1
17
0
Order By: Relevance
“…To the best of our knowledge, the growth, medium pH and membrane potential have never been measured simultaneously. Generally, the characteristic IAA-induced changes in the membrane potential of the coleoptile cells that were observed here (the initial, transient depolarisation followed by the hyperpolarisation of the membrane) are in good agreement with other authors [ 22 , 23 , 24 , 25 , 42 , 57 , 58 ]. However, taking into account our experimental conditions (membrane potential was measured simultaneously with the growth and medium pH), it should be pointed out that these characteristic changes differed in their kinetics compared to those in the articles cited above.…”
Section: Discussionsupporting
confidence: 93%
“…To the best of our knowledge, the growth, medium pH and membrane potential have never been measured simultaneously. Generally, the characteristic IAA-induced changes in the membrane potential of the coleoptile cells that were observed here (the initial, transient depolarisation followed by the hyperpolarisation of the membrane) are in good agreement with other authors [ 22 , 23 , 24 , 25 , 42 , 57 , 58 ]. However, taking into account our experimental conditions (membrane potential was measured simultaneously with the growth and medium pH), it should be pointed out that these characteristic changes differed in their kinetics compared to those in the articles cited above.…”
Section: Discussionsupporting
confidence: 93%
“…The organisation of the cortical microtubules was also analysed, and it was shown that naphthazarin changed the IAA-induced microtubule reorientation. These results suggest that naphthazarin decreased the growth of maize coleoptile cells via a broad spectrum of effects [44].…”
Section: Discussionmentioning
confidence: 99%
“…For the combination of naphthazarin with lawsone or 1,4-naphthoquinone, it should be pointed out that the inhibitory effect on the auxin-induced growth and proton extrusion of the maize coleoptile segments was stronger compared to the individual action of any of the naphthoquinones that were tested (see [38,44]). This synergetic effect was significantly more visible at a concentration of 1 nM, particularly when naphthazarin was combined with 1,4-naphthoquinone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formerly, Laskowki proposed that the longitudinal reorientation of microtubules follows growth rate decline, but that it must be triggered by factors distinct from the change of elongation rate [45]. More recently, the idea that a direct and rapid longitudinal reorientation of microtubules by auxin is part of the mechanism by which auxin inhibits growth (akin to Hypothesis A, recall Figure 1) has been a matter of debate [8,46,47]. Based on this recent discussion and on the findings presented here, we recognize that the reorientation of microtubules into longitudinal arrays is not likely to be a direct prerequisite for inhibition of root cell elongation by auxin.…”
Section: Discussionmentioning
confidence: 99%